Peran Orang Tua dalam Meningkatkan Motivasi Belajar Anak di Kelurahan Bandar Klippa Kecamatan Percut Sei Tuan - Tobing, Minar Trisnawati (CV. Creative Tugu Pena, 2022)
Education is a process of educating and guiding students to achieve certain goals in the form of positive changes in children. Education starts from the family, namely parents. Parents are the first madrasa for children. This study aims to determine the role of parents in increasing children's learning motivation in Bandar Klippa Village, Percut Sei Tuan District. This type of research is a field descriptive, which takes place in Banda Village. Klippa Percut Sei Tuan District. The data sources used are primary and secondary data sources. The techniques used in data collection are observation methods, documentation methods, and interview methods. Based on research conducted through interviews, observations, and documentation that the roles played by parents in increasing children's learning motivation are parents as role models, parents as child facilitators, and parents as child motivators, as for the form of motivators that can be given by parents to children are attention, reward, reward, praise, and punishment. Based on the data analysis, it is concluded and understood that the role of parents in increasing children's learning motivation is quite good. This can be seen from interviews and observations that the role of parents has been well realized by parents in Bandar Klippa Village, Percut Sei Tuan District. Keywords: Increasing Learning Motivation, The Role of Parents, Children Learning Motivation